Faktor-Faktor Prediktor Investment Opportunity Set Dan Firm Value Pada Perusahaan Propertydan Real Estate Yang Terdaftar Di Bei - Rita Amelinda dan Indra Widjaja (Universitas Tarumanagara, 2019)
Great integration and similar point of view between stakeholders are essential to build an optimal firm value. As alongwith firm value, most of investor also view rate of return in their investment. Therefore, investment opportunity set could also become a mediator to optimize firm value. Recently ,in a crisis and financial distress condition, these two main variables lead to dilemma for some company such. This study aims to find out about the factors which predict the firm value and investment opportunity set. The sample of this research consist on 39 companies in property and real estate industry sector which listing in Indonesia Stock Exchange (IDX) between 2012 until 2016 period. This research used panel regression analysis with fixed effect method to test their hypothesis. The conclusion of this study indicate that simultaneously, leverage, financial risk, free cash flow, institutional ownership, and working capital affect the firm value significantly. While, partially, only leverage, free cash flow, and working capital which affect the firm value significantly. On the other hand, investment opportunity set has only perfectly mediating between financial risk and institutional ownership to firm value and partially mediating leverage to firm value.